2012
DOI: 10.1177/0091270011419854
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of MK‐5046, a Bombesin Receptor Subtype‐3 (BRS‐3) Agonist, in Healthy Patients

Abstract: MK-5046 is an orally active, potent, selective agonist of the orphan G protein–coupled receptor bombesin receptor subtype-3 (BRS-3) that is under evaluation for treatment of obesity. We report the safety, tolerability, pharmacokinetics, and pharmacodynamics of oral doses of MK-5046 (10-160 mg) in a double-blind, randomized, placebo-controlled study in healthy and obese male volunteers. MK-5046 exposure increased dose proportionally, and MK-5046 was eliminated with an apparent terminal half-life of 1.5 to 3.5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…As noted, the effects of the BRS-3 system on Tb are likely secondary to its primary role in energy homeostasis. This makes the concern that BRS-3 agonists will produce clinical hyperthermia unlikely, and is consistent with the lack of observed Tb changes in men treated with MK-5046 (30). The realization that adult humans can and do expend energy via BAT activation has brought attention to BAT (24) and highlighted the potential for drugs that activate BAT as a treatment for obesity (36).…”
Section: E684 Brs-3 Regulation Of Body Temperature Terizing Brs3mentioning
confidence: 61%
“…As noted, the effects of the BRS-3 system on Tb are likely secondary to its primary role in energy homeostasis. This makes the concern that BRS-3 agonists will produce clinical hyperthermia unlikely, and is consistent with the lack of observed Tb changes in men treated with MK-5046 (30). The realization that adult humans can and do expend energy via BAT activation has brought attention to BAT (24) and highlighted the potential for drugs that activate BAT as a treatment for obesity (36).…”
Section: E684 Brs-3 Regulation Of Body Temperature Terizing Brs3mentioning
confidence: 61%
“…Peptide #1 had a more rapid onset and shorter duration of action for each. This difference was not due to a difference in stability with the two agonists, as previous studies had demonstrated that each is stable under incubation conditions at 37°C for at least 1 hour (Mantey et al, 1997;Sebhat et al, 2011;Reitman et al, 2012). Compared with previous studies that investigated the kinetics/duration of action of peptide and nonpeptide agonists, our results are similar to those with the CCK1-receptor nonpeptide agonist SR146131 (Bignon et al, 1999;Schaeffer et al, 2000), where the nonpeptide had a more prolonged duration of the action in stimulating [Ca 21 ] i when it was compared with an equally effective dose of the natural agonist CCK-8S.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have reported that the nonpeptide MK-5046 [(2S)-1,1,1-trifluoro-2-[4-(1H-pyrazol-1-yl)phenyl]-3-(4-{[1-(trifluoromethyl)cyclopropyl]methyl}-1H-imidazol-2-yl)propan-2-ol] is an orally active, potent, and selective BRS-3 agonist (Sebhat et al, 2011;Guan et al, 2011;Reitman et al, 2012), with activity in mice, rats, dogs , and humans (Reitman et al, 2012). Furthermore, recently a selective peptide antagonist Bantag-1 [Boc-Phe-His-4-amino-5-cyclohexyl-2,4,5-trideoxypentonyl-Leu-(3-dimethylamino) benzylamide N-methylammonium trifluoroacetate] also has been reported (Guan et al, 2010;Feng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown if this hypertensive effect of MK-5046 would be more pronounced in elderly or patients with diminished baroreflex function. The adverse effects of BRS-3 agonists attenuate with continued dosing (14,37,46). We have not investigated attenuation in mice, making this an important question for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…One BRS-3 agonist, MK-5046, transiently increased blood pressure in rats, dogs, and humans (but has not been studied in mice) (15,46). A different BRS-3 agonist also increased blood pressure, while a third agonist reduced it, making it unclear if the blood pressure effects are mediated via BRS-3 (15).…”
Section: Mk-5046 a Bombesin-like Receptor 3 (Brs-3) Agonist Increasmentioning
confidence: 99%